Bogolyubov averaging and normalization procedures in nonlinear mechanics. IV - Lopatin, A.K.; Mitropolskiy, Yu.A. (Український математичний журнал, 1995)
In this paper, we apply the theory developed in parts I-III to some classes of problems. We consider linear systems in zero approximation and investigate the problem of invariance of integral manifolds under perturbations. Unlike nonlinear systems, linear ones have centralized systems, which are always decomposable. Moreover, restrictions connected with the impossibility of diagonalization of the coefficient matrix in zero approximation are removed. In conclusion, we apply the method of local asymptotic decomposition to some mechanical problems.